What pelvic radiation disease symptoms are experienced by patients receiving external beam radiotherapy and a high-dose-rate brachytherapy boost for prostate cancer? - Halkett, Georgia; Short, M.; Aoun, Samar; Joseph, D.; Bydder, S.; Meng, X.; Spry, N. (2017)
Purpose: Research describing proctitis or pelvic radiation disease symptoms of prostate cancer patients one year after external beam radiotherapy (EBRT) plus high-dose-rate (HDR) brachytherapy is limited. This study aimed to assess prostate cancer patients' pelvic radiation disease symptoms from baseline to 12 months post-radiotherapy. Material and methods: Men with prostate cancer referred for EBRT and HDR brachytherapy were recruited. Patients' age, diagnosis, staging, PSA, past medical history, and treatment were recorded. Pelvic radiation disease symptoms were assessed via the Phase III EORTC proctitis module. Patients completed questionnaires before radiotherapy (baseline) and at one, three, six, and 12 months afterwards. To assess acute toxicity, symptoms one month after radiotherapy were compared with baseline. To assess post-treatment recovery, symptoms at three, six, and 12 months post radiotherapy were compared with one month. Symptom changes over time were assessed with linear mixed effect models. Results: Two hundred and sixty-six patients were recruited. Mean scores were below 2 at all time-points. The proportion of patients experiencing symptoms were also calculated. Linear mixed effect models showed that time-point, age, and T-stage were associated with some pelvic radiation disease symptoms. Conclusions: Patients receiving EBRT plus HDR brachytherapy to the prostate experienced mild pelvic radiation disease symptoms. Determining the proportion of patients w ith symptoms provided the most meaningful data.